Role of diagnostic laparoscopy in chronic abdominal pain: Experience in a rural area: Diagnostic laparoscopy in chronic pain in abdomen - Kanake, Vijay; Sundaravadanam, Vighnesh; Mangam, Shubhangi; Bhalavi, Vijay (Chronic Diseases Journal, 2023)
BACKGROUND: Chronic abdominal pain is a frequent cause of surgical consultation. This study is conducted to evaluate usefulness of laparoscopy in diagnosis of chronic abdominal pain so as to reduce suffering and depression associated with condition. This study aims to define the role of diagnostic laparoscopy in chronic abdominal pain. METHODS: A hospital-based prospective study was conducted in the Department of Surgery, Shri Vasantrao Naik Government Medical College, Yavatmal, India, a tertiary care center in the rural area from January 1, 2016 to June 30, 2017 with 50 patients to evaluate the role of laparoscopy in patients with chronic abdominal pain. All the patients underwent diagnostic laparoscopy with methodical inspection of the whole abdominal cavity. Statistical analysis was done using SPSS software. RESULTS: The majority of the patients (36%) were in the age group of 21-30 years with women affected more (66%). The most common symptom was pain (100%) for more than 4-5 months. Laparoscopic findings were appendicitis (30%) followed by Koch’s abdomen (26%), adhesions (24%), sub-acute intestinal obstruction (SAIO) (8%), ovarian cyst (4%), and hernia (2%) which were treated accordingly. Resolution of pain was seen in 94% of the patients over a follow-up period of 3 months. CONCLUSION: Diagnostic laparoscopy is a safe and effective procedure in the evaluation of patients with chronic abdominal pain in a rural area. It also provides an opportunity to perform the therapeutic procedure in the same setting thereby reducing the overall cost of treatment.